SUCCESSIVE FORAMINIFERAL FAUNAS AND INFERRED PALAEOENVIRONMENTS ASSOCIATED WITH THE POSTGLACIAL (HOLOCENE) MARINE TRANSGRESSION, GULF ST VINCENT, SOUTH AUSTRALIA - Cann J.H.; Murray-Wallace C.V.; Riggs N.J.; Belperio A.P. (My University, 2006)
Gulf St Vincent is one of a pair of elongate, triangular, shallow water embayments into the southern coast of continental Australia. From the southern floor of this embayment, within a shallow basin-like depression where present-day water depth is about 40 m, vibracore SV23 recovered c. 4 m of late Quaternary sediments. The uppermost 1.5 m of this core comprises postglacial (Holocene) marine deposits; six radiocarbon ages for the interval 64-130 cm downcore are all around 10 000 cal. yr BP, while two for 18-24 cm are several thousand years younger. Radiocarbon analysis of an oyster shell at 154 cm yielded a minimum age of c. 37 000 cal. yr BP. Well-preserved benthic foraminifera are abundant in all the recovered sediments. The early phase of Holocene marine sedimentation in Gulf St Vincent was marked by the development of a marginal marine, perhaps lacustrine to estuarine environment, as signified by the presence of oogonia, gypsum crystals and the foraminifera Miliolinella labiosa and Elphidium cf. articulatum. Development of seagrass meadows followed; these were inhabited by Nubecularia lucifuga and Discorbis dimidiatus. As the marine transgression proceeded, the environment remained somewhat restricted, as indicated by Ammonia beccarii, but numbers of this species declined giving way to Massilina milletti as conditions began to resemble those of the modern Gulf St Vincent. Culmination of the transgression provided the conditions necessary for the dominance of Ammobaculites reophaciformis and Flintina triquetra. A. reophaciformis and F triquetra therefore record the final episode of the transgression and transition to the modern, deeper water environment. At several lower horizons they also occur as conspicuous spikes, equivalent to their modern abundance. These spikes, which coincide with equivalent decreased numbers of A. beccarii, are interpreted to represent downward bioturbation of the overlying deeper water sediment.
Keywords: FORAMINIFERA; BIOTURBATION; OOGONIA; HOLOCENE; MARINE TRANSGRESSION; POSTGLACIAL; GULF ST VINCENT; SOUTH AUSTRALIA; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен